Malignant cutaneous melanomas: pathological anatomy - de los Santos, Julio (Cirugía del Uruguay, 1974)
The malignant melanomas of the skin can appear in melanoblasts of seemingly normal skin, in melanotic precancerous scales of the Dubreuilh-Hutchinson type, or in junction nevus. These develop from a precancerous stage to a state of melanoma in situ, and then t0 a form of infiltrating melanoma. There are two forms of evolution: one slow of superficial localization, and the other quick with deep infiltration in adjacent tissues. Also three forms of anatomopathological tumors: 1) superficial infiltrating melanomas or originated by premelanotic melanosis; 2) melanomas of lentigomelanosis or lentigo malignant origin; 3) nodular melanomas. Deep infiltration affects the process and diagnosis of melanoma. Five different degrees are established according to the depth of cutaneous peentration. Lymphatic diffusion has gr.eat importance in the evolution, and through this satel!itosis and lymph nodes invasion is produced. Perfusion treatments destroy the so-called in transit metastases: and under these circumstances Alkeran has proved to be very effective in sone of our cases.